Use of Nonpharmacologic Interventions by Adults With High-Impact Chronic Pain in the United States: A Cross-Sectional Analysis - Natasha L. Parman; Robert H. Schmicker; Sean D. Rundell (Pain Research and Management)
Conclusion: Our findings highlight that most US adults with HICP have recently used NPIs to manage their pain, but the use of specific NPIs varied considerably. The odds of using NPIs were different depending on the locations of bothersome pain. Future work should examine barriers for access to specific NPIs or the use of NPIs by locations of bothersome pain.